1974
DOI: 10.1126/science.185.4154.857
|View full text |Cite
|
Sign up to set email alerts
|

Streamflow Greatly Reduced by Converting Deciduous Hardwood Stands to Pine

Abstract: Fifteen years after two experimental watersheds in the southern Appalachians had been converted from a mature deciduous hardwood cover to white pine, annual streamflow was reduced about 20 centimeters (20 percent) below that expected for the hardwood cover. Streamflow was reduced during every month, with the largest monthly reductions (1.5 to 3.5 centimeters) occurring in the dormant and early growing seasons.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
110
3
1

Year Published

2000
2000
2018
2018

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 191 publications
(121 citation statements)
references
References 4 publications
7
110
3
1
Order By: Relevance
“…Thus, converting forest type or controlling the canopy height and stem density of coniferous forest could be the tools for regulating streamflow. Converting temperate coniferous forests into broadleaved forests has also been shown to increase water yield because winter interception loss is larger for evergreen compared to broadleaf deciduous forest (Swank and Douglass, 1974). This management practice could be applied to the uniform precipitation monsoon regions such as northern Japan to increase water yield (Komatsu et al, 2008a).…”
Section: Regulating Streamflowmentioning
confidence: 99%
“…Thus, converting forest type or controlling the canopy height and stem density of coniferous forest could be the tools for regulating streamflow. Converting temperate coniferous forests into broadleaved forests has also been shown to increase water yield because winter interception loss is larger for evergreen compared to broadleaf deciduous forest (Swank and Douglass, 1974). This management practice could be applied to the uniform precipitation monsoon regions such as northern Japan to increase water yield (Komatsu et al, 2008a).…”
Section: Regulating Streamflowmentioning
confidence: 99%
“…Thus, such losses tend to be greater for evergreen forests than for deciduous forests (Hibbert, 1967;Schulze, 1982) and may be expected to be larger for fast-growing forests with high rates of carbon storage than for slow-growing forests. Consequently, afforestation with fast-growing conifers on non-forest land commonly decreases the flow of water from catchments and can cause water shortages during droughts (Hibbert, 1967;Swank and Douglass, 1974). Vincent (1995), for example, found that establishing high-water-demanding species of pines to restore degraded Thai watersheds markedly reduced dry season streamflows relative to the original deciduous forests.…”
Section: 4]mentioning
confidence: 99%
“…The initial tree density at the time of planting was 3000 trees/ha, but is now about 1000-1200 trees/ha. With the same rainfall, more streamflow discharges from natural old deciduous forests because of the smaller evapotranspiration that occurs compared with coniferous forests [30,31]. The main factor influencing the recession characteristics was the evapotranspiration derived by different forest cover.…”
Section: Differences Between Gc and Gd Catchmentsmentioning
confidence: 99%